Intraoperative assessment of margins in breast conservative surgery—still in use?. Issue 1 (24th May 2014) - Thill, Marc; Baumann, Kristin; Barinoff, Jana; Rubio, Isabel T.; Dixon, J. Michael
<x xml:space="preserve">Abstract</x> A positive margin in breast conserving surgery is associated with an increased risk of local recurrence. Failure to achieve clear margins results in re‐excision procedures. Methods for intraoperative assessment of margins have been developed, such as frozen section analysis, touch preparation cytology, near‐infrared fluorescence optical imaging, x‐ray diffraction technology, high‐frequency ultrasound, micro‐CT, and radiofrequency spectroscopy. In this article, options that might become the method of choice in the future are discussed. J. Surg. Oncol. 2014 110:15–20. © 2014 Wiley Periodicals, Inc.